Evaluation of Occupational Burnout and Job Satisfaction among Endodontists in Iran - Hosseini, Bahareh; Manochehrifar, Hamed; Shahravan, Arash; Yazdani, Aseman; Malek Mohammadi, Tayebeh; Mohammadzadeh, Iman; Nekouei , Amir Hossein (Iranian Endodontic Journal, 2024)
Introduction: Occupational burnout has been introduced as one of the most critical social problems. The present study aimed to evaluate occupational burnout among a group of Iranian endodontists. Material and Methods: Seventy-two Iranian endodontists participated in this cross-sectional study by completing the abbreviated Maslach Burnout Inventory (aMBI), consisting of one questionnaire in three domains. The data were analyzed with SPSS 21, using the chi-squared test, correlation test, and linear regression. Results: Concerning occupational burnout, 2.9% of the participants had severe emotional exhaustion, 4.2% exhibited an intense feeling of decreased accomplishment, 67.2% exhibited moderate occupational burnout, and 78.9% of the participants were satisfied with their job. Of all the variables, only the years elapsed since graduation had an inverse and significant correlation with occupational burnout among endodontists. Conclusion: The overall mean scores of endodontists showed a moderate rate of occupational burnout compared to the standard mean scores in this field. Recent graduates exhibited higher scores.